2022
DOI: 10.1136/bmjopen-2021-054188
|View full text |Cite
|
Sign up to set email alerts
|

Modern contraceptive use among adolescent girls and young women in Benin: a mixed-methods study

Abstract: ObjectivesThe study aimed to assess the determinants of modern contraceptive method use among young women in Benin.DesignA mixed-methods design.Setting and participantsWe used the Benin 2017–2018 Demographic and Health Survey datasets for quantitative analysis. Data collection was conducted using multiple-cluster sampling method and through household survey. Qualitative part was conducted in the city of Allada, one of the Fon cultural capitals in Benin. The participants were purposively selected.OutcomesContra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
1
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 27 publications
3
27
1
4
Order By: Relevance
“…Unmarried respondents were more likely to use contraceptive methods than married respondents. This is in line with a previous national survey conducted in Ethiopia(18), a study conducted in the Amhara region among female university students (34), and among adolescent girls and young women in Benin (24); however, this is not similar to the study conducted in Gondar town among female college students (35) and Dilla town secondary and preparatory schools (19), as well as a community-based study conducted in the Tigray region among female students, which showed that contraceptive use among married respondents is more likely to use contraceptive methods than unmarried respondents(36).…”
Section: Discussionsupporting
confidence: 92%
“…Unmarried respondents were more likely to use contraceptive methods than married respondents. This is in line with a previous national survey conducted in Ethiopia(18), a study conducted in the Amhara region among female university students (34), and among adolescent girls and young women in Benin (24); however, this is not similar to the study conducted in Gondar town among female college students (35) and Dilla town secondary and preparatory schools (19), as well as a community-based study conducted in the Tigray region among female students, which showed that contraceptive use among married respondents is more likely to use contraceptive methods than unmarried respondents(36).…”
Section: Discussionsupporting
confidence: 92%
“…Contraceptive use among adolescents was very low (17.4%), similar to Mali (17.1%) [ 28 ], but higher than Uganda (9.4%) [ 6 ], Benin (8.5%) [ 29 ], Nigeria (14.8%) [ 30 ], Nepal (11.9%) [ 31 ] and Zambia (12%) [ 32 ], according to previous studies. Nonetheless, the Government of Rwanda has put considerable efforts in family planing and reducing unwanted pregnancies as part of its 2030 Family Planing country commitment agenda.…”
Section: Discussionmentioning
confidence: 63%
“…Compared to the rst analysis of only sexually active adolescents, sensitivity analysis results clearly indicate that modern contraceptive use increases with age, a signi cant trend noted in age groups of 17, 18 and 19 years (Table 4). [29], Nigeria (14.8%) [30], and Nepal (11.9%) [31], according to previous studies. This low uptake could be a result of various factors, including a lack of awareness and limited sex education in schools and households, poor access to services, misconceptions regarding contraceptive effects on reproduction, and negative cultural implications [32,33].…”
Section: Resultsmentioning
confidence: 58%